A new proposed Weibull distribution of inclusion size and its correlation with rolling contact fatigue life of an extra clean bearing steel. (September 2019) - Cao, Zhaoxi; Shi, Zhiyue; Yu, Feng; Wu, Guilin; Cao, Wenquan; Weng, Yuqing
Highlights: Nonmetallic inclusions of GCr15 are analyzed quantitatively by the rotated bending test. Two parameters Weibull distribution function is applied to analyze the statistical distribution. Relationship between nonmetallic inclusions and the rolling contact fatigue life is built experimentally and theoretically. Abstract: The rolling contact fatigue life (RCF-life ( N )) of an extra clean bearing steel of GCr15 is examined by Thrust rolling test. The variation of RCF-life with failure probability ( P ( N )) is analyzed by the Weibull function, which shows a very nice linear relationship between ln( N ) and ln(−ln(1 −  P ( N ))). The nonmetallic inclusions measured by rotated bending fatigue test and Aspex are evaluated by the statistics of the inverse value of the inclusions (1/ D In ), which shows a perfect Weibull distribution between ln(1/ D In ) and ln(−ln(1 −  P (1/ D In ))). Based on the similarity of the two Weibull distributions, the correlation between RCF-life and the largest oxide inclusion size is derived to be N  =  k (1/ D In ) p both experimentally and theoretically. This finding not only gives us a clear understanding of the size and distribution effects on the variation of the subsurface controlled RCF-life, but enable the prediction of RCF-life based on the characterization of inclusions and the Paris law on crack propagation.